1983
DOI: 10.1152/ajprenal.1983.244.2.f210
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cold diuresis in the rat

Abstract: The effect of cold exposure (CE) on renal water excretion has not been clearly delineated. Conscious rats were exposed to decreased ambient temperature (15 degrees C). Forty-five minutes of CE resulted in reversible increases in urine flow and decreases in urine osmolality. The diuresis was not due to a diminished response to vasopressin (VP), as the antidiuresis associated with 500 microU of Pitressin given to water-diuresing rats was comparable at 15 and 30 degrees C. To determine whether the diuresis was du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The diuresis was not due to a diminished response to AVP. The glomerular filtration rate, renal blood flow, Na+ excretion, and osmolar clearance were equivalent during control and cold conditions [119]. In anesthetized rats hypothermia (Tre 28°C) increased the urine flow (sixfold) and urine Na+ excretion (sevenfold) and decreased urine osmolality and plasma AVP level (-50%).…”
Section: Insulin Glucagon Glucosementioning
confidence: 87%
See 1 more Smart Citation
“…The diuresis was not due to a diminished response to AVP. The glomerular filtration rate, renal blood flow, Na+ excretion, and osmolar clearance were equivalent during control and cold conditions [119]. In anesthetized rats hypothermia (Tre 28°C) increased the urine flow (sixfold) and urine Na+ excretion (sevenfold) and decreased urine osmolality and plasma AVP level (-50%).…”
Section: Insulin Glucagon Glucosementioning
confidence: 87%
“…Nonosmotic suppression of AVP in response to cold exposure has been noted in animals [97,119,120] and humans [59,121], and may be the basis of the cold diuresis. Cold exposure (4°C) for 30min increased systolic blood pressure and plasma NE (twofold) level and decreased the plasma volume (-7.8% ) and plasma AVP level (-35 % ) in men with no change in Tre• The changes in systolic blood pressure, NE, and AVP were significant as early as 2min after the beginning of exposure.…”
Section: Insulin Glucagon Glucosementioning
confidence: 99%
“…This diuresis was seen 60 min after the animals were placed in the cold and would correspond well to our own electrophysiological and urine flow findings. More recently, Morgan et al (1983) reported a diuresis in cold-exposed rats over a 45 min time period. Thus, it would appear that, in most previous studies, only single urine samples were taken over more lengthy sampling periods which may, in part, explain the conflicting results.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased levels of this hormone have been reported in humans (Segar & Moore, 1968) and rats (Morgan, Anderson, Ellis & Berl, 1983), whereas increased levels in unanaesthetized dogs (Sadowski et al 1972) and no consistent changes in young pigs (Forsling et al 1976) have been observed.…”
Section: Introductionmentioning
confidence: 97%
“…Acute and chronic exposures to cold induced diuresis probably via different mechanisms: the former via a reduction in plasma AVP (2,10,13) and the latter by suppression of renal V 2 receptors without reduction of plasma AVP. Kidney weights of LE and VD rats were increased equally by cold exposure, suggesting that AVP may not be involved in coldinduced renal hypertrophy.…”
Section: Discussionmentioning
confidence: 99%